Solar-Driven Photoelectrochemical Water Oxidation over an n‑Type Lead–Titanium Oxyfluoride Anode - Hirayama, Naoki; Nakata, Hiroko; Wakayama, Haruki; Nishioka, Shunta; Kanazawa, Tomoki; Kamata, Ryutaro; Ebato, Yosuke; Kato, Kosaku; Kumagai, Hiromu; Yamakata, Akira; Oka, Kengo; Maeda, Kazuhiko (Journal of the American Chemical Society, 2019)
Mixed-anion compounds (e.g., oxynitrides and oxysulfides) are potential candidates as photoanodes for visible-light water oxidation, but most of them suffer from oxidative degradation by photogenerated holes, leading to low stability. Here we show an exceptional example of a stable, mixed-anion water-oxidation photoanode that consists of an oxyfluoride, Pb2Ti2O5.4F1.2, having a band gap of ca. 2.4 eV. Pb2Ti2O5.4F1.2 particles, which were coated on a transparent conductive glass (FTO) support and were subject to postdeposition of a TiO2 overlayer, generated an anodic photocurrent upon band gap photoexcitation of Pb2Ti2O5.4F1.2 (λ <520 nm) with a rather negative photocurrent onset potential of ca. −0.6 V vs NHE, which was independent of the pH of the electrolyte solution. Stable photoanodic current was observed even without loading a water oxidation promoter such as CoO x . Nevertheless, loading CoO x onto the TiO2/Pb2Ti2O5.4F1.2/FTO electrode further improved the anodic photoresponse by a factor of 2–3. Under AM1.5G simulated sunlight (100 mW cm–2), stable water oxidation to form O2 was achieved using the optimized Pb2Ti2O5.4F1.2 photoanode in the presence of an applied potential smaller than 1.23 V, giving a Faradaic efficiency of 93% and almost no sign of deactivation during 4 h of operation. This study presents the first example of photoelectrochemical water splitting driven by visible-light excitation of an oxyfluoride that stably works, even without a water oxidation promoter, which is distinct from ordinary mixed-anion photoanodes that usually require a water oxidation promoter.